2022
DOI: 10.1155/2022/6094663
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences in Bone Mineral Density between Multiple Sites in the Same Individual: An Elderly Cadaveric Study

Abstract: Bone mineral density (BMD) is known to vary based on various factors, and the degree of variation is site-specific. However, few studies have investigated the relationship between bone density at trabecular bone-rich and cortical bone-rich sites in the same individual. In this study, we attempted to measure BMD at multiple sites using whole-body computed tomography images taken immediately after death and to clarify the similarities and differences between skeletal sites. Additionally, we aimed to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Moreover, BMD is well known to vary according to various factors, including age, the loading environment, bone microstructures and ossi cation processes of bone speci c sites, and the degree of variation is site speci c in the same individual [33]. Our results showed that positive and negative effects of a high-fat diet on osteopenia or osteoporosis in humans may depend on idiographic sites.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, BMD is well known to vary according to various factors, including age, the loading environment, bone microstructures and ossi cation processes of bone speci c sites, and the degree of variation is site speci c in the same individual [33]. Our results showed that positive and negative effects of a high-fat diet on osteopenia or osteoporosis in humans may depend on idiographic sites.…”
Section: Discussionmentioning
confidence: 59%
“…NAFLD, however, was linked in a Korean study to risk variables for men's femoral neck bone density and protective factors for women's lumbar spine bone density [ 13 ]. Each of these studies mentioned above explored the relationship between bone mineral density and fatty liver in different parts of the body, such as the femur, the femoral neck, and the lumbar spine; however, bone mineral density varies throughout the body [ 18 ], and there is a paucity of the literature exploring the relationship between nonalcoholic fatty liver disease and ankle bone mineral density in older adults.…”
Section: Introductionmentioning
confidence: 99%